Characterization and pathogenicity of a naturally reassortant and recombinant infectious bursal disease virus in China. Issue 4 (29th October 2021) - Feng, Xufei; Zhu, Ning; Cui, Yongqiu; Hou, Lei; Zhou, Jianwei; Qiu, Yonghui; Yang, Xiaoyu; Liu, Changzhe; Wang, Dedong; Guo, Jinshuo; Sun, Tong; Shi, Yongyan; et al.
Abstract: Infectious bursal disease virus (IBDV), an Avibirnavirus, is the pathogen of infectious bursal disease, which is a severely immunosuppressive disease in 3–15‐week‐old chickens. Different phenotypes of IBDV, including classical, variant, very virulent (vv) and attenuated IBDV, have been reported in many chicken‐rearing countries worldwide. Here, we isolated and identified a naturally reassortant and recombinant IBDV (designated GXB02) from 20‐day‐old chickens with clinicopathological changes of infectious bursal disease (IBD) in Guangxi Province, China. Whole genomic sequencing showed that the strain GXB02 simultaneously has both reassortant and recombinant characteristics with segments A and B being derived from recombinant intermediate vaccine strain and classic strains of IBDV. Segment A of strain GXB02 was incorporated into the skeleton of an intermediate IBDV vaccine strain (W2512), where the breakpoints of two recombinant events located at nucleotide positions 1468 and 1648 were replaced by reassortant vvIBDV (PK2) and vvIBDV (D6948) of segment A, respectively. We used this GXB02 strain to inoculate 21‐day‐old specific‐pathogen‐free chickens to evaluate its pathogenicity. Strain GXB02 has clinicopathologic characteristics of IBD with severe bursal lesions, as evidenced by necrosis, depletion of lymphocytes, and follicle atrophy, indicating that reassortment with classical strains in segment B or/and recombination with very virulent strains increased pathogenicity of the strain GXB02 in chickens. These findings provide important insights into the genetic exchange between classic and attenuated strains of IBDV with two recombinant events occurring at the intermediate derivative segment A with vvIBDV strains, thereby increasing the difficulty of prevention and control of IBD due to novel reassortant–recombinant strains.